Endothelial Cell Focal Adhesion Regulates Transendothelial Migration and Subendothelial Crawling of T Cells - Lee, Jaehyun; Song, Kwang Hoon; Kim, Taeyeob; Doh, Junsang (Frontiers in Immunology, 2018)
Leukocytes circulating in the blood stream leave out of blood vessels and infiltrate into inflamed tissues to perform immune responses. Endothelial cells (ECs) lining interior of the post-capillary venules regulate various steps of leukocyte extravasation. In response to inflammatory signals, ECs up-regulate adhesion molecules and produce/present chemokines to support firm adhesion and intraluminal crawling of leukocytes. They also remodel junctions to facilitate leukocyte transendothelial migration (TEM). While roles of apical/lateral components of EC layers in regulating leukocyte extravasation have been extensively investigated, relatively little attention has been paid to the basal part of EC layers comprising subendothelial spaces. In this study, we employed interference microscopy (IRM), a microscopy technique specialized for label-free visualization of cell-substrate contact, to study detailed dynamic interactions between basal layers of ECs and T cells underneath EC layers. For TEM, T cells on EC monolayer extended protrusions through junctions to explore subendothelial spaces, and EC focal adhesions (EC-FAs) acted as physical barrier for the protrusion. Therefore, preferential TEM occurred through junctions where near junction FA (NJ-FA) density of ECs was low. After TEM, T cells performed subendothelial crawling (SEC) with flattened morphology and reduced migration velocity due to tight confinement. T cell SEC mostly occurred through gaps formed in between EC-FAs with minimally breaking EC-FAs. TNF- treatment significantly loosened confinement in subendothelial spaces and reduced NJ-FA density of ECs, thus remodeled basal parts of EC layer to facilitate leukocyte extravasation.